Zimbabwe : 2011 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Zimbabwe. (IMF Staff Country Reports; Country Report, 2011)
Stronger policies, favorable external environment, and notable improvement in the humanitarian situation supported a nascent economic recovery in Zimbabwe. Executive Directors welcomed this, and urged authorities to take advantage of the favorable external environment to strengthen their macroeconomic framework. They stressed the need to strengthen the fiscal position and expressed concern about rising vulnerabilities in the banking system. They welcomed the authorities strategy for arrears clearance. Directors agreed that the Staff Monitored Program (SMP) would help establish a track record of sound policies, and encouraged the authorities to continue timely data reporting.